Strategi Pengembangan Ekowisata terhadap Ekonomi Lokal pada Desa Wisata Fatumnasi - Clarce Sarliana Maak; Maria Prudensiana Leda Muga; Novi Theresia Kiak (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2022)
The purpose of the research is the socio-economic conditions of the local community in the tourist village that can support the presence of tourists during their activities in the tourist area and apply a regional development strategy as an area with an ecotourism model to strengthen the existence of the Fanumasi tourist area as well as a source for tourism. The method used is qualitative descriptive by using SWOT analysis. The results obtained from this study are the need for the government to socialize the importance of nature conservation as the main tool of ecotourism and special training to attract youth around tourist attractions in marketing services